Development of Pythagorean Theorem Content Worksheets Based on Creative Problem Solving to Facilitate Mathematical Reasoning Skills - Suanto, Elfis; Rianti, Efni; Armis, Armis; Zulnaidi, Hutkemri (UNNES JOURNAL, 2024)
Mathematical reasoning ability is one of the most important parts of mathematics learning. However, the facts show that students' mathematical reasoning ability is still low, especially in the context of the Pythagorean theorem. One attempt to facilitate this is using students' worksheets based on creative problem solving (CPS). This research aims to develop valid and practical student' worksheets. It refers to the 4D development model, which includes defining, designing, developing, and disseminating. The instruments used are validation and practicality questionnaire sheets. The results of the validity assessment of students' worksheets were very valid, with an average percentage of 95,07%. The results of the practicality assessment of students' worksheets were very practical, with an average rate of 89,38%. Thus, it is in accord with the valid and practical requirements, so the worksheet is usable. This research aims to make it easier for students to build knowledge independently in mathematics learning so that mathematical reasoning abilities can be facilitated. Kemampuan penalaran matematis (KPM) menjadi salah satu aspek yang terpenting dalam pembelajaran matematika, namun fakta menunjukkan KPM peserta didik masih rendah khususnya pada konten teorema Pythagoras. Salah satu upaya untuk memfasilitasi masalah tersebut dengan menggunakan Lembar kerja peserta didik (LEMBAR KERJA SISWA) berbasis Creative Problem Solving (CPS). Tujuan penelitian ini adalah mengembangkan LEMBAR KERJA SISWA yang valid dan praktis. Penelitian pengembangan ini mengacu pada model pengembangan 4D yang meliputi define, design, develop, dan disseminate. Instrumen yang digunakan adalah angket validasi dan angket praktikalitas. Hasil analisis data angket validasi diperoleh bahwa LEMBAR KERJA SISWA dikategorikan sangat valid dengan persentase rata-rata yaitu 95,07%. Hasil analisis data angket praktikalitas diperoleh bahwa LEMBAR KERJA SISWA dikategorikan sangat praktis dengan persentase rata-rata yaitu 89,38%. Maka, LEMBAR KERJA SISWA pada penelitian ini telah memenuhi syarat valid dan praktis sehingga dapat digunakan dalam kegiatan pembelajaran. Implikasi dari penelitian ini adalah untuk mempermudah peserta didik dalam membangun pengetahuan secara mandiri pada pembelajaran matematika sehingga kemampuan penalaran matematis dapat terfasilitasi.